Production Scheduling Mathematical Model in Garment Industry - Van Thanh, Nguyen (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2021)
In this paper, the author introduces about building the support system of production schedule, based on the linear programming model, exploiting effectively Branch and Bound (BnB) algorithms in Lingo software. In addition, the result of the study is the software that supports production schedule based on the C# programming language, friendly interface makes the operator easy to use. After the implementation and final test, the research model is applied to the case of the garment company to support the production schedule, reduces the number of orders delayed, shorten the production time to increase profits for the company.